Meteorological and Emission Influences on PM2.5 Concentration in South Korea during the Seasonal Management: A Case of December 2019 to March 2020 - Son, Kyuwon; Bae, Minah; You, Seunghee; Kim, Eunhye; Kang, Yoon Hee; Bae, Changhan; Kim, Yoonha; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2020)
Abstract The nation-wide PM2.5 concentration from December 2019 to March 2020 (2019 Winter) in South Korea was observed as low as 24 μg/m3, showing the lowest seasonal mean PM2.5 concentrations for the last five years. Consequently, the PM2.5 concentration during the Seasonal Management has dropped by 26% and 23% compared to those for the same months in 2018 (2018 Winter), and the previous three years (2016~2018), respectively. In this study, the observations and air quality simulations with a set of fixed anthropogenic emissions were incorporated to quantitatively separate the meteorology and emission influences on the PM2.5 change in South Korea during the 2019 Winter. The results show that meteorology and emission-driven influence has decreased the national mean PM2.5 concentrations during the 2019 Winter by 9% and 18%, respectively when compared to the 2018 Winter. On the other hand, the same comparison to PM2.5 concentrations for the previous three years explained approximately 2% increase and 24% drop with meteorology and emission-driven infuence, respectively. Monthly mean PM2.5 changes have varied for each month and exhibited the largest drop in February 2020 by 24% when compared to February 2019 (a 27% drop from the previous 3-year mean for the month). It may refect the abrupt PM2.5-related emission reductions in Northeast Asia after the COVID-19 pandemic. Air quality simulations with perturbed emissions presented that an increase of South Korean domestic impact and a decrease of foreign emission impact between the 2018 and 2019 Winters. It represents that South Korean domestic efforts to reduce PM2.5 concentrations become more efficient under the meteorology condition during the 2019 Winter.
Keywords: Emission; Influence; Meteorology; PM2.5; The seasonal management